Keseimbangan Berbagi Informasi dan Memahami Batasan dalam Mencegah Terjadinya Oversharing - Nurkhofifah Awini; Ahmad Ridfah (PT PUSTAKA CENDEKIA GROUP, 2025)
Oversharing behavior, namely the tendency to share personal information excessively on social media, is becoming an increasingly widespread phenomenon and causing various psychological impacts, such as decreased self-confidence, violation of privacy, and emotional stress. The lack of individual awareness of the limits of sharing information indicates the need for educational interventions that can improve understanding and digital literacy. This study aims to convey psychoeducational messages about the dangers of oversharing through digital poster media. The poster was distributed online and has been viewed by 70 people, with 40 of them willing to fill out a questionnaire via Google Form to assess understanding of the contents of the poster. This activity was carried out for 14 days in March 2025. The response results showed 95% positive acceptance of the psychoeducational material and 80% increased awareness of respondents regarding the importance of managing personal information. These findings indicate that simple psychoeducational media can be a strategic alternative in fostering wiser information sharing behavior in the digital age.